The impact of national non-pharmaceutical interventions (‘lockdowns’) on the presentation of cancer patients - Purushotham, Arnie; Roberts, Graham; Haire, Kate; Dodkins, Joanna; Harvey-Jones, Elizabeth; Han, Lu; Rigg, Anne; Twinn, Claire; Pramesh, Conjeevaram; Ranganathan, Priya; Sullivan, Richard; Aggarwal, Ajay (Ecancermedicalscience, 2021)
One of the most ignored aspects of the COVID-19 pandemic has been the impact of public health measures by governments on wider health and welfare. From March 2020, hospitals in the UK saw a dramatic reduction in patients with cancer presenting due to multifactorial reasons. The impact of the pandemic on patients with cancer in the South East London Cancer Alliance was studied. The specific aims were (1) to examine the reduction in cancer diagnoses during the first wave of the pandemic and (2) to examine the stage of diagnosis of patients with cancer presenting during the pandemic compared with that of patients presenting before the pandemic. There was an 18.2% reduction in new cancer diagnoses (an estimate of 987 cancers), when compared with 2019. This fall in cancer diagnoses was most marked in patients with prostate (51.4%), gynaecological (29.7%), breast (29.5%) and lung (23.4%) cancers. There was an overall 3.9% increase in advanced stage presentation (Stages 3 and 4), with an overall 6.8% increase in Stage 4 cancers during this period. The greatest shifts were seen in lung (increase of 6.3%, with an 11.2% increase in Stage 4 cancer alone) and colorectal (5.4%) cancers. For prostate cancer, there was an increase in 3.8% in those presenting with Stage 4 disease. For breast cancer, there was an 8% reduction in patients diagnosed with Stage 1 cancer with commensurate increases in the proportion of those with Stage 2 disease. The experiences in cancer are a salient warning that pandemic control measures and policy need to balance all health and welfare. Alternative strategies need to be adopted during further waves of the current and any future pandemic to ensure that patients with cancer are prioritised for diagnosis and treatment to prevent late-stage presentation and an increase in avoidable deaths.